Arthrogryposis in a calf - C VENKATESAN,; WILLIAM, B J; V RAMASWAMY, (The Indian Journal of Animal Reproduction, 2003)
A case of arthrogryposis in a calf and its surgical management has been reported.
Keywords: Arthrogryposis; hind limbs; musculoskeletal system